Grain refinement of pure magnesium by the addition of calcium carbonate. (20th March 2019) - Zhang, L; Liu, X R; Huang, H
Abstract: The effect of CaCO3 addition on grain refinement of pure magnesium was studied in the present work. Results show that remarkable grain refinement in pure magnesium was achieved with the addition of CaCO3 because of the formation of in situ CaO particles, which can act as effective heterogeneous nuclei for magnesium grains. With the addition of 0.2 wt% CaCO3, the average grain size of pure magnesium was significantly reduced from 3860 μ m to 240 μ m, and further addition only resulted in negligible refinement. After 10 min of holding, the pure magnesium with the addition of 0.2 wt% CaO3 indicated a very fine equiaxed grain structure across the entire section, which was somewhat retained for holding time up to 120 min.